Age normalization of face photo by image decomposition and reconstruction - Han, Yunlong (2017)
Aging is an inevitable process of human and it is affected signiﬁcantly by many factors such as health, gender, race, and lifestyle, which make it very difficult to establish an accurate modeling of aging in human faces. Aging normalization or modeling for special age group can predict one's appearance, which help to find the missing children and track criminal suspects and terrorists etc.